2020
DOI: 10.1073/pnas.1914286117
|View full text |Cite|
|
Sign up to set email alerts
|

Small-molecule targeted recruitment of a nuclease to cleave an oncogenic RNA in a mouse model of metastatic cancer

Abstract: As the area of small molecules interacting with RNA advances, general routes to provide bioactive compounds are needed as ligands can bind RNA avidly to sites that will not affect function. Small-molecule targeted RNA degradation will thus provide a general route to affect RNA biology. A non–oligonucleotide-containing compound was designed from sequence to target the precursor to oncogenic microRNA-21 (pre–miR-21) for enzymatic destruction with selectivity that can exceed that for protein-targeted medicines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
187
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(201 citation statements)
references
References 23 publications
6
187
0
1
Order By: Relevance
“…A RIBOTAC targeting pre-miR-21, dubbed TGP-21 RIBOTAC, was recently reported that is based on the dimeric binding compound TGP-21 (Table S1, ESI †). 190 TGP-21 was first validated in MDA-MB-231 TNBC cells, reducing levels of mature miR-21 and increasing levels of pre-miR-21, in accordance with its mechanism of inhibiting Dicer processing (Table S1, ESI †). 190 The binding dimer also increased expression of programmed cell death protein 4 (PDCD4) and phosphatase and tension homolog (PTEN), two proteins that are translationally repressed by miR-21.…”
Section: Targapremir-21 Ribotac (Tgp-21 Ribotac): Targeting Pre-mir-2mentioning
confidence: 91%
See 2 more Smart Citations
“…A RIBOTAC targeting pre-miR-21, dubbed TGP-21 RIBOTAC, was recently reported that is based on the dimeric binding compound TGP-21 (Table S1, ESI †). 190 TGP-21 was first validated in MDA-MB-231 TNBC cells, reducing levels of mature miR-21 and increasing levels of pre-miR-21, in accordance with its mechanism of inhibiting Dicer processing (Table S1, ESI †). 190 The binding dimer also increased expression of programmed cell death protein 4 (PDCD4) and phosphatase and tension homolog (PTEN), two proteins that are translationally repressed by miR-21.…”
Section: Targapremir-21 Ribotac (Tgp-21 Ribotac): Targeting Pre-mir-2mentioning
confidence: 91%
“…190 TGP-21 was first validated in MDA-MB-231 TNBC cells, reducing levels of mature miR-21 and increasing levels of pre-miR-21, in accordance with its mechanism of inhibiting Dicer processing (Table S1, ESI †). 190 The binding dimer also increased expression of programmed cell death protein 4 (PDCD4) and phosphatase and tension homolog (PTEN), two proteins that are translationally repressed by miR-21. 190 Additionally, invasion assays confirmed TGP-21's ability to inhibit the invasive phenotype of MDA-MB-231 cells.…”
Section: Targapremir-21 Ribotac (Tgp-21 Ribotac): Targeting Pre-mir-2mentioning
confidence: 91%
See 1 more Smart Citation
“…However, further research needs to be undertaken to evaluate their efficacy, bioavailability and safety before entering the clinical studies. Beyond these three examples, therapies targeting viral RNAs [187,188], RNA cleavage through RNase recruitment [189,190], mRNA translation by inhibiting eukaryotic translation initiation factors [191], as well as premature translational termination caused by nonsense mutations [192], are being developed. With respect to the huge number of RNA-targeted therapies in preclinical studies and clinical trials, it is apparent that these therapies will form a key part of personalised, precision medicine in the future.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Three approaches have been used to develop miR inhibitors: (i) oligonucleotidebased antagomirs to bind to the mature miRs via base pairing (8); (ii) small molecules that target pri-or pre-miR structures found at functional Dicer or Drosha processing sites, thereby inhibiting biogenesis (9)(10)(11); and (iii) small molecules that target miR precursor structures to trigger cleavage of the RNA target (12)(13)(14). One of the challenges with targeting some miRs specifically with oligonucleotides is that family members can have the same or similar sequences (15,16).…”
Section: /Bodymentioning
confidence: 99%